ANALISIS GENANGAN PADA PENGENDALIAN BANJIR SUNGAI SARIO KOTA MANADO - Utami, Panca Desy Puji (Sistem Infrastruktur Teknik Sipil (SIMTEKS), 2024)
Sario River is located in Manado City and Minahasa Regency. The city of Manado is located on the northern tip of Sulawesi Island and is the largest city in the North Sulawesi as well known as the capital of North Sulawesi Province. The Geography coordinate is between 10o30'-10 o40' North latitude (N) and 1240 o 40'00" - 1260 o50'00" East Longitude (E). Floods of the sario river, that have occurred periodically and often have due to the capacity of the river that cannot accommodate the amount of flood discharge. Analysis of inundation in flood control ,aims to determine the extent and height of inundation that occurs due to flood overflow. Based on the results of the analysis of the maximum flood discharge obtained by the HECHMS method is 112,284 m3/dt. From these results it is obtained that the maximum discharge at the discharge observer point on the Sario/Ranotana river at the same time is 115,73 m3/det. To handle the situation that exist in the Sario river, a hydraulics analysis is carried out by simulating with HECRAS.  There are several modeling scenarios that are analyzed including existing conditions, normalization handling and combination of normalization and embankments.